Enhanced production of erythritol and mannitol by Yarrowia lipolytica in media containing surfactants - Rakicka,Magdalena (2016)
Abstract Various chemical compounds, including surfactants, when introduced to culture media may increase the permeability of cellular membranes and thereby affect the quantity of metabolites excreted by cells. The aim of the present study was to evaluate the impact of detergents including Triton X-100, Span 20 and Tween 80 on erythritol production from glycerol by Yarrowia lipolytica Wratislavia K1 in a shake-flask experiment, batch and fed-batch cultures. When Span 20 was added to a fed-batch culture with glycerol as a carbon source (300 g L-1), erythritol production increased by 15% compared to the culture without the surfactant where it reached 142 g L-1 after 5 days, which corresponded to 0.47 g g-1 yield and productivity of 1.1 g L-1 h-1. Therefore, it was concluded that Span 20 considerably enhanced the production of this polyol from glycerol.